Pengaruh Tarif Pajak Efektif, Ukuran Perusahaan dan Kepemilikan Asing terhadap Transfer Pricing - Zidane, Bagus Muhammad; Purwatiningsih, Purwatiningsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Transfer pricing remains a crucial issue in multinational corporate governance, particularly in developing countries like Indonesia, where aggressive tax planning can erode the domestic tax base. This study investigates the influence of Effective Tax Rates, Company Size, and Foreign Ownership on transfer pricing practices in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was employed, utilizing purposive sampling to select 10 companies, resulting in 50 firm-year observations over five years. Secondary data were obtained from the financial statements of the sampled companies. The study applied panel data regression analysis, conducted using EViews 12 software. The findings show that, collectively, effective tax rate, company size, and foreign ownership significantly influence transfer pricing. However, partial analysis reveals that effective tax rate and company size have no significant effect, while foreign ownership significantly affects transfer pricing practices. These findings suggest that foreign investors may play a role in shaping transfer pricing strategies, possibly due to cross-border operational structures or tax minimization motives. This study contributes to the literature on tax policy and corporate governance in emerging markets.